Short Communication: Genetic diversity of the IGF2 gene as a source of genetic marker for halal authentication - ANTI DAMAYANTI HAMDANI; MADIHAH .; RR. BHINTARTI SURYOHASTARI; DEWI PETI VIRGIANTI; RAHAYU FITRIAYANI WANGSA PUTRIE (Smujo International, 2018)
Hamdani AD, Madihah, Suryohastari RB, Virgianti DP, Putrie RFW. 2018. Genetic diversity of the IGF2 gene as a source of genetic marker for halal authentication. Nusantara Bioscience 10: 203-209. The main issue of halal authenticity is the availability of reliable and rapid analytical methods to identify animal species in raw and processed food. The two most popular procedures for identifying the source of the meat are protein-based and DNA-based methods, including mass spectroscopy (MS) using a peptide marker or PCR based DNA marker, respectively. This study aims to investigate the genetic diversity of insulin-like growth factor 2 (IGF2) gene, mainly from porcine (Sus scrofa) and bovine (Bos taurus) as a source of genetic marker for halal authentication by in-silico analysis using bioinformatic tools. Multiple sequence alignment and phylogenetic tree construction of IGF2 protein sequences from representative species of mammals, birds, and fishes showed the paraphyletic relationship between the IGF2 protein of S. scrofa and B. taurus. Protein structure analysis revealed differences in helical structures near the carboxyl end of the protein, while gene analysis showed different number of exon and motifs. By in-silico analysis, we have designed a peptide marker from amino acids at position of 93-107 (S. scrofa) and 93-112 (B. taurus) from peptide preptin region that resulted in different pattern of mass spectrum between the two species. We have also identified two DNA markers that can be detected by PCR using two primers sets designed from the IGF2 transcript sequences, to examine the presence of porcine in the sample. Thus, this study provides new genetic predictive markers, derived from the IGF2 gene, to identify the source of meat for halal authentication.